Gambaran Kelengkapan Pengisian Kuesioner Autopsi Verbal Kematian Ibu Di Puskesmas Wilayah Kabupaten Ciamis - Maulani Agustina; Imas Masturoh (Jurnal Persada Husada Indonesia, 2018)
A verbal autopsy is a search for a series of events, circumstances, symptoms, and signs of disease that lead to death through interviews with family or other parties who know the sick condition of the deceased. In the implementation of verbal autopsy there are problems regarding the completeness of filling out the verbal autopsy questionnaire, making it difficult for doctors to determine the cause of maternal death. The purpose of this study was to find out the complete picture of filling in a verbal autopsy questionnaire for maternal deaths at the Ciamis District Health Office. The type of research used was quantitative descriptive with populations and samples using a total sampling of 15 maternal death forms. Data collection methods used are observation and interviews. The results showed that the largest completeness was 60% for filling direct causes. The largest completeness was 73.3% in antenatal care items, items aged <20 years old were found 6.7% complete, age 20-35 years 60% complete. The item number of children ≤3 mostly 53.3% complete, items number of children> 3 obtained 26.7% complete. Item pregnancy distance ≥2 years is 40% complete. Items are late looking for help 33% complete. Late referenced items are 60% complete. And items that are late in making decisions are 40% complete. This incompleteness is caused by the lack and difficulty of obtaining information from families, private hospitals and midwives, midwives sometimes are lazy to fill and inaccurate, and the unavailability of Standard Operating Procedures for the AV questionnaire.